Analysis of heart rate variability after exercise with oscillatory pole - Ogata, C. M. [UNESP]; Abreu, L. C.; Vanderlei, F. M. [UNESP]; Navega, M. T. [UNESP]; Valenti, V. E. [UNESP] (Silicea - Poligraf, 2016)
Aim. To evaluate the acute effects of exercise with oscillatory pole on cardiac autonomic modulation. Material and methods. The study was performed on 18 young adult males aged between 18 and 25 years old. The subjects remained at rest for 10 minutes, after the rest period, the volunteers performed the exercises with the oscillatory pole. Immediately after the exercise protocol, the volunteers remained seated at rest for 30 minutes. We evaluated the geometric indexes of heart rate variability. Results. The SD1 index increased 25-30 minutes after exercise compared to rest and the SD2 index decreased 5-10 minutes and 10-15 minutes compared with 15-20 minutes after exercise. Conclusion. A single session of exercise with oscillatory pole increased the parasympathetic component of heart rate variability and reduced the overall variability of heart rate in the initial 15 minutes after exercise
Keywords: Autonomic nervous system; Cardiovascular system; Exercise therapy; Heart rate; Oscillatory pole; Young